Developmental Anomalies of the Inferior Vena Cava and its Tributaries: What the Radiologist Needs to Know? - Verma, Mansi; Pandey, Niraj Nirmal; Ojha, Vineeta; Kumar, Sanjeev; Ramakrishnan, Sivasubramanian (Indian Journal of Radiology and Imaging, 2022)
Inferior vena cava (IVC) can be involved by a wide gamut of developmental anomalies owing to its complex embryogenesis. Developmental anomalies of the IVC are not infrequent, seen in approximately 8.7% of the general population. Although most of the anatomical variations are asymptomatic, identification of these variations is important before planning any vascular surgery or interventional procedure in relation to the IVC to avoid inadvertent complications. Conventional venography has largely been replaced by noninvasive cross-sectional imaging modalities for detecting IVC abnormalities. Ultrasonography, often used for initial evaluation, is highly operator-dependent and the infrarenal part of IVC is often obscured by bowel gases. While magnetic resonance imaging is devoid of radiation risks, its use is limited due to limited availability and the frequent need for sedation. Computed tomography (CT) venography plays a pivotal role in the detection of these anomalies as it has an excellent spatial resolution along with availability of multiple postprocessing tools such as multiplanar reconstruction with generation of maximum intensity projection and volume-rendered images. This pictorial review focuses on the embryogenesis of IVC, various developmental anomalies of the IVC and its tributaries, their appearance on CT venography and conceivable clinical relevance.
Keywords: computed tomography; developmental anomalies; inferior vena cava